Instilling Islamic Values in Elementary School Students: A Case Study of the R2SC Method (Routine, Role Models, Spontaneity, and Conditioning) - Moh Wardi; Ismail Ismail; Supandi Supandi; Hodairiyah Hodairiyah; Moh. Zainol Kamal (STAI Hubbulwathan Duri, 2025)
Instilling Islamic values in primary school students is crucial for fostering moral and spiritual character from an early age. This study examines the effectiveness of the R2SC technique (Routine, Role Model, Spontaneity, and Conditioning) in developing Islamic character in young learners by integrating structured activities and contextual learning. A qualitative case study approach was employed, with data collected through direct observation, in-depth interviews with educators and students, and document analysis of R2SC implementation in an Islamic elementary school. Thematic analysis was used to identify key patterns and insights. The findings indicate that the R2SC technique effectively instills Islamic values in students. Routine practices, such as communal prayers and religious activities, reinforce spiritual discipline. Educators and school staff serve as role models, demonstrating Islamic behaviors. Spontaneity in daily interactions helps students internalize values in real-life contexts, while conditioning ensures a supportive environment for continuous reinforcement. The study highlights the practical benefits of the R2SC approach in Islamic character education. It provides educators with a structured yet flexible methodology to integrate religious teachings into everyday school life, making moral education more impactful. The R2SC technique is a comprehensive method for Islamic character development in primary schools. Future research should explore its adaptability in different cultural and educational settings to enhance its global applicability and effectiveness.